Therapeutic Potential of Wharton’s Jelly Mesenchymal Stem Cells for Diabetes: Achievements and Challenges - Kamal, Mohamed M.; Kassem, Dina H. (Frontiers in Cell and Developmental Biology, 2020)
Diabetes mellitus is an alarming metabolic disease in which insulin secreting β-cells are damaged to various extent. Unfortunately, although currently available treatments help to manage the disease, however, patients usually develop complications, as well as decreased life quality and increased mortality. Thus, efficient therapeutic interventions to treat diabetes are urgently warranted. During the past years, mesenchymal stem cells (MSCs) have made their mark as a potential weapon in various regenerative medicine applications. The main fascination about MSCs lies in their potential to exert reparative effects on an amazingly wide spectrum of tissue injury. This is further reinforced by their ease of isolation and large ex-vivo expansion capacity, as well as demonstrated multipotency and immunomodulatory activities. Among all the sources of MSCs, those isolated from umbilical cord-Wharton’s jelly (WJ-MSCs), have been proved to provide a great source of MSCs. WJ-MSCs do not impose any ethical concerns as those which exist regarding ESCs, and represent a readily available non-invasive source, and hence suggested to become the new gold standard for MSC-based therapies. In the current review, we shall overview achievements, as well as challenges/hurdles which are standing in the way to utilize WJ-MSCs as a novel efficient therapeutic modality for diabetes mellitus.